2021
DOI: 10.1016/j.heliyon.2021.e07182
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of thin-layer drying and modelling for mango slices and the influence of differing hot-air drying methods on quality

Abstract: This study compared the thin-layer drying kinetics of hot-air methods, namely, convective oven drying (OVD), uncontrolled solar drying (UAD) and modified ventilation greenhouse solar drying (MVD). Additionally, the effects of these drying techniques on colour, rehydration characteristics and microstructure of Tommy Atkin mango slices were investigated. The experiments were conducted on mango slices of three different thicknesses: 3 mm, 6 mm and 9 mm. The drying curves generated from the experimental data revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…This was possibly attributed to the high moisture diffusion capacity at high temperature since the increased drying temperature could accelerate the activity of water molecules [ 15 ]. Similar observations were reported during HAD of mango slices [ 19 ] and Boletus edulis [ 10 ].…”
Section: Resultssupporting
confidence: 88%
“…This was possibly attributed to the high moisture diffusion capacity at high temperature since the increased drying temperature could accelerate the activity of water molecules [ 15 ]. Similar observations were reported during HAD of mango slices [ 19 ] and Boletus edulis [ 10 ].…”
Section: Resultssupporting
confidence: 88%
“…Further more, higher thermal energy promotes the movement of water molecules in the food resulting in a reduction in drying time with increasing drying temperature [38]. Thes results are quite similar to previous studies reported on different plant food such a blanched pumpkin slices [39], butterfly pea flowers [10], and mango slices [40].…”
Section: Drying Kineticssupporting
confidence: 87%
“…The VD and HAD treatment groups displayed the fastest DR during the decreasing stage. As the drying process proceeded, the internal moisture of lemon slices decreased, while the energy consumption gradually became higher, resulting in a gradual DR decline (Mugodo & Workneh, 2021). Therefore, the drying process of the internal moisture diffusion control of lemon slices was similar to that of dragon fruit, dendrobium flower, and apples (Shu et al., 2020).…”
Section: Resultsmentioning
confidence: 99%